Rethinking the Conceptual Model of Governance: Insights from Gen Z’s Political Entrepreneurship Prototypes in Digital Civics and Democratic Innovations - Sobari, Wawan (Indonesian Association for Public Administration (IAPA), 2025)
This study re-examines conceptual models of governance through an analysis of political entrepreneurship prototypes created by Gen Z students, focusing on digital civics and democratic innovation. Dominant governance models—networked governance (Rhodes, 1996; Sørensen & Torfing, 2007), interpretive governance (Bevir & Rhodes, 2016), and state-centric governance (Pierre & Peters, 2018)—are based on formal institutional relations and have not yet accommodated the experimental micro-arena driven by young citizens using digital technology. Using a qualitative content analysis of 28 prototypes (12 digital civics and 16 democratic innovations), this study examined how Gen Z design collective decision-making processes. The findings suggest that digital civics build political literacy, and that democratic innovations facilitate policy co-production. This study proposes the concept of governance as co-produced micro-arenas–small-scale collective decision arenas designed by young political entrepreneurs–to expand governance theory to cross-generational collaborative ecosystems.